THE ROLE OF THE MANPOWER OFFICE IN INCREASING LABORA PRODUCTIVITY - Shintia Lekatompessy; Hamjah Bonso; Asdar Djabar (Universitas Djuanda, 2025)
This study aims to analyze the role of the Manpower Office of Biak Numfor Regency in enhancing labor productivity through training and skill development programs. The informants of this study include employees of the Manpower Office, training participants, and partner companies involved in the programs. Data collection techniques employed were in-depth interviews, participant observation, and document review related to implementing training and job placement programs. The collected data were analyzed using descriptive qualitative methods with a thematic analysis approach, linking field findings to theories of human resource development and labor productivity. The results indicate that the Manpower Office has conducted competency-based training per the Indonesian National Work Competency Standards (SKKNI). Yet, challenges remain, such as uneven facility distribution, limited practical equipment, and a job placement system that is not yet optimally integrated. Theoretically, improving labor productivity requires enhancements in training infrastructure and strengthening synergistic partnerships among the government, businesses, and trainees. In conclusion, although the training programs have been implemented, optimizing their outcomes depends on improving the quality of facilities and establishing a more effective job placement system.